Study on genetic diversity of Castanopsis phuthoensis Luong in Phu Tho province, Vietnam by RAPD markers - Thọ, Nguyễn Văn; Linh, Lê Thị Mai; Viễn, Nguyễn; Tiến, Phạm Quang (Vietnam Journal of Biotechnology, 2016)
Castanopsis phuthoensis Luong is an endemic tree species of Phu Tho province, only distributed narrowly in forest rehabilitation in two communes belonging to Doan Hung district with density of this species is very low, only from 3.1 to 11.1 trees per hectare. Diameter distributions of the species of number of trees is characterized by curve style with a peak in 20cm or 24cm diameter classes. As it is difficult to find the seedling in the nature, research on forest structure, relations between tree species and genetic diversity is very necessary to define method of conservation for this species. In this study, we used RAPD markers to study on genetic diversity of Castanopsis phuthoensis Luong. The random amplified polymorphic DNA (RAPD) based on the polymeraze chain reaction (PCR) detects nucleotide sequence polymorphism using a single 10mer of arbitrary nucleotided sequence. The RAPD technology has quickly gained widespread acceptance and application because it providesa tool for genetic analysis that have not previously benefited the use of molecular markers. In this study, ten random primers to analyse the genetic diversity of 15 Castanopsis phuthoensis Luong samples that were collected from Phu Tho province, Vietnam. 9 RAPD primers gave DNA polymorphism and 01 RAPD primer OPA20 gave not DNA polymorphism. In the analysis region 0.25-2 kb, there were 56 DNA fragments amplified and 34 DNA fragments were polymorphic. Genetic similarity coefficients of 15 Castanopsis phuthoensis Luong samples ranged from 0.55- 0.95. The phylogenetic tree of 15 samples are divided into two main groups. As results of RAPD-PCR analysis, these samples were collected from the homologous geographical locations and the genetic diversity of 15 samples is not high. Therefore, it is necessary to conserve the "Castanopsis phuthoensis Luong"